Long-term exposure to road traffic noise, ambient air pollution and cardiovascular risk factors in the HUNT and Lifelines cohorts - Cai,Y; Hansell,A; Blangiardo,M; Burton,P; de,Hoogh K; Doiron,D; Fortier,I; Gulliver,J; Hveem,K; Mbatchou,S; Morley,D; Stolk,R; et al. (European Heart Journal, 2017)
AimsBlood biochemistry may provide information on associations between road traffic noise, air pollution, and cardiovascular disease risk. We evaluated this in two large European cohorts (HUNT3, Lifelines).Methods and resultsRoad traffic noise exposure was modelled for 2009 using a simplified version of the Common Noise Assessment Methods in Europe (CNOSSOS-EU). Annual ambient air pollution (PM10, NO2) at residence was estimated for 2007 using a Land Use Regression model. The statistical platform DataSHIELD was used to pool data from 144 082 participants aged ≥20 years to enable individual-level analysis. Generalized linear models were fitted to assess cross-sectional associations between pollutants and high-sensitivity C-reactive protein (hsCRP), blood lipids and for (Lifelines only) fasting blood glucose, for samples taken during recruitment in 2006–2013. Pooling both cohorts, an inter-quartile range (IQR) higher day-time noise (5.1 dB(A)) was associated with 1.1% [95% confidence interval (95% CI: 0.02–2.2%)] higher hsCRP, 0.7% (95% CI: 0.3–1.1%) higher triglycerides, and 0.5% (95% CI: 0.3–0.7%) higher high-density lipoprotein (HDL); only the association with HDL was robust to adjustment for air pollution. An IQR higher PM10 (2.0 µg/m3) or NO2 (7.4 µg/m3) was associated with higher triglycerides (1.9%, 95% CI: 1.5–2.4% and 2.2%, 95% CI: 1.6–2.7%), independent of adjustment for noise. Additionally for NO2, a significant association with hsCRP (1.9%, 95% CI: 0.5–3.3%) was seen. In Lifelines, an IQR higher noise (4.2 dB(A)) and PM10 (2.4 µg/m3) was associated with 0.2% (95% CI: 0.1–0.3%) and 0.6% (95% CI: 0.4–0.7%) higher fasting glucose respectively, with both remaining robust to adjustment for air/noise pollution.ConclusionLong-term exposures to road traffic noise and ambient air pollution were associated with blood biochemistry, providing a possible link b